Political Connections and Tax Avoidance: Does Audit Quality Moderate The Relationship? - Maria Goreti Kentris Indarti; Jacobus Widiatmoko (Universitas Pendidikan Indonesia, 2023)
This study aims to investigate the effect of political connections and executive character on tax avoidance, as well as examine the role of audit quality variables in this relationship. This research uses moderated regression to analyze 343 data from manufacturing companies listed on the Indonesian Stock Exchange in 2019-2021. The findings of this study suggest that political connections and executive character have a positive effect on tax avoidance. Another important finding is that audit quality, as an external governance mechanism, can reduce the impact of political connections and executive character on tax avoidance. On the other hand, tax avoidance is not directly impacted by audit quality. This study supports agency theory which emphasizes the importance of governance mechanisms in minimizing agency conflicts, in particular the presence of quality auditors as an external governance mechanism is able to reduce management's tendency to commit tax avoidance. For the Directorate General of Taxes, the findings of this study provide important input in determining tax policy to be more effective by conducting tighter oversight of companies that are politically connected and have executives with a risk-taking character. This research offers audit quality, which is an external governance mechanism as a solution to mitigate tax avoidance which is motivated by political connections and the character of executives who dare to take risks.